Forgotten ureteral stents: a systematic review of literature - Xiaochuan Wang; Zhengguo Ji; Peiqian Yang; Jun Li; Ye Tian (BMC Urology, 2024)
Abstract Background The forgotten ureteral stents (FUS) is one of the late complications of stent placement. This systematic review summarized different aspects of FUS and focused on the problems and solutions related to FUS. Methods This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. PubMed® and Embase® were searched from inception until October 1st, 2022. Eligible studies were those defining FUS as a stent unintentionally left in situ longer than at least 2 months. Results Total 147 studies with 1292 patients were finally included. The mean indwelling time of FUS was 33.5 months (range from 3 months to 32 years). The most common initial cause for stent placement was adjunct treatment to urolithiasis (79.2%). The major forgetting reasons were patient-related (83.9%), which included poor compliance, lapse in memory, and misconceptions about the necessity of timely removal. Primary presenting complaints were flank pain (37.3%), lower urinary tract symptoms (33.3%), and hematuria (22.8%). Encrustation (80.8%) and urinary tract infections (40.2%) were the most common complications detected in patients with FUS. Computed tomography evolving as a preferred imaging test (76.1%) was indispensable for evaluating encrustation, migration, fracture and other complicated situations in patients with FUS. Besides, evaluation of kidney function and infection status was also of great importance. Multiple and multimodal procedures (59.0%) were often necessitated to achieve the stent-free status, and were mostly endoscopic procedures. Cystoscope was most commonly used (64.8%). Retrograde ureteroscopy (43.4%) and antegrade stent removal (31.6%) were often used when dealing with more complicated situations. Extracorporeal shockwave lithotripsy (30.4%) was often used as adjunctive to other endoscopic procedures, but it sometimes failed. The decision regarding the choice of treatment is based on the volume and site of encrustation, the direction of migration, the site of fracture, kidney function and other urinary comorbidities. Conclusions FUS not only pose hazard to patients’ health, but also impose a huge economic burden on medical care. Thorough preoperative evaluation is fundamental to developing the treatment strategy. The management of FUS should be individualized using different treatment modalities with their advantages to minimize patients’ morbidities. Prevention is better than cure. Strengthening health education and setting a tracking program are of great importance to the prevention of FUS.